Die Protokolle des cisleithanischen Ministerrates1867-191 Band VIII/ Erster Weltkrieg Teilband I: Teilband 1: 23. Juli 1914 - 22. November 1916 - Fischer-Nebmaier, Wladimir (Verlag der Österreichischen Akademie der Wissenschaften, 2023)
Volume Vlll/1 treats the first two years of World War 1, until the death of Francis Joseph on November 21, 1916. The government was headed by Karl Stürgkh, until his assassination in October 1916, followed by the short-termed cabinet Ernest Koerber II. Among the most important issues were the ending of civil society, the way into economic martial-absolutism, notably including food supply, as weil as the humanitarian consequences of war, and wartime Dualism.